THE RELATIONSHIP BETWEEN SEXUAL KNOWLEDGE ABOUT PHYSICAL CHANGES AND ANXIETY IN FACING PUBERTY IN ADOLESCENTS AT SMPN 1 MARGOYOSO PATI - Moh. Zahron Rois; Feri Catur Yuliani; Dwi Puji Susanti; Akbar Amin Abdullah (RADJA PUBLIKA, 2025)
Puberty is a developmental phase in which children begin to transition from asexuality to sexual maturity. This period is marked by the development of reproductive organs and the ability to reproduce. This study aims to analyze the relationship between the level of sexual knowledge regarding physical changes and the level of anxiety in facing puberty in adolescents at SMPN 1 Margoyoso Pati. The sampling technique used was simple random sampling, a method of randomly selecting samples from a population without regard to specific levels within the population. Furthermore, respondents were selected using purposive sampling. The anxiety measurement instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire. The level of sexual knowledge regarding physical changes during puberty shows that 49 respondents (58.33%) have knowledge in the good category, 27 respondents (32.14%) are in the sufficient category, and 8 respondents (9.53%) are in the poor category. There is a significant relationship between sexual knowledge related to physical changes and anxiety in facing puberty in adolescents at SMPN 1 Margoyoso Pati. Adolescents with good sexual knowledge tend to be better able to reduce or even avoid anxiety when entering puberty.